STUDY ON MACROSCOPIC AND MICROSCOPIC MECHANICAL BEHAVIOR OF SILICA REINFORCED SILICONE RUBBER COMPOSITES - SHI PingAn; QIU Yong; WAN Qiang (Jixie qiangdu)
Through observing and analyzing the microstructure of the materials by SEM,the interfacial bonding and Strengthen Mechanism of silicone rubber reinforced by silica were investigated. Then,based on micro-mechanics and fracture mechanics theories,and the fracture energy of interface between silica and silicone rubber was introduced to reflect the interfacial mechanical characteristics,then the quantity was deduced that could reflect the reinforced effect of different silica feature and different silica content,and the analytical expression of reinforced material properties with fracture energy and the silica volume fraction were respectively observed. To prove the accuracy of the analytical expressions,the relative experimental data with theoretical curve were compared. This study provides the theoretical basis and technical support for the structural optimization and performance evaluation of silicon rubber and silicone foam material.